THE FOCUSES OF TEACHER’S WRITTEN FEEDBACK ON STUDENTS’ DESCRIPTIVE TEXT AT THE TENTH GRADE OF SMAN 1 TANAH JAWA - Dinda Chintya Sinaga; Masitowarni Siregar; Rafika Dewi Nasution (Universitas Negeri Medan, 2020)
This study was aimed at finding out the teacher written feedback focuses and purpose on students writing descriptive text at SMA Negeri 1 Tanah Jawa. This study used descriptive qualitative research design. The participants of this study were an English teacher and 36 students grade X of SMA Negeri 1 Tanah Jawa. In this research, the data source was the students’ descriptive text writing. It was collected after their writing was given written feedback by the teacher. The instruments for collecting data were documentation and interview. There are six focuses on teacher written feedback. The focuses are language form, text functions, content, creative expression, the writing process, and genre. Based on the analysis of the students’ writing, it is figured out that the teacher’s written feedback mostly focuses on language form namely grammar. Based on the interview, from six purposes namely provides information for both teacher and students, provides advice to the students, provides students language input, motivates the students, and leads students toward autonomy, the result showed that the teacher has been fullfiled all thoses purposes of written feedback.